2015
DOI: 10.1038/srep16463
|View full text |Cite|
|
Sign up to set email alerts
|

Can silicon carbide serve as a saturable absorber for passive mode-locked fiber lasers?

Abstract: The study presents a novel demonstration of a passively mode-locked erbium-doped fiber laser (EDFL) that is based on a silicon carbide (SixC1−x) saturable absorber. When the C/Si composition ratio is increased to 1.83, the SixC1−x film transforms from two-photon absorption to nonlinear saturable absorption, and the corresponding value reaches −3.9 × 10−6 cm/W. The Si-rich SixC1−x film cannot mode lock the EDFL because it induced high intracavity loss through two-photon absorption. Even when a stoichiometric Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(51 reference statements)
2
6
1
Order By: Relevance
“…The smallest decrease of reflectance was observed for the DLC:Si film containing 12 at.% of Si, and the largest one for the film containing 29.7 at.% Si. It should be mentioned that C/Si ratio (1.82) for DLC:Si film containing 29.7 at.% of silicon was nearly the same (1.83) as reported by Cheng et al [25] for carbonenriched SiC film, which exhibited saturable absorption effect.…”
Section: Optical Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…The smallest decrease of reflectance was observed for the DLC:Si film containing 12 at.% of Si, and the largest one for the film containing 29.7 at.% Si. It should be mentioned that C/Si ratio (1.82) for DLC:Si film containing 29.7 at.% of silicon was nearly the same (1.83) as reported by Cheng et al [25] for carbonenriched SiC film, which exhibited saturable absorption effect.…”
Section: Optical Propertiessupporting
confidence: 79%
“…There are two possible explanations of the different nonlinear properties in these films with nearly identical C/Si atomic concentration ratio. On one hand, in the present study a larger amount of oxygen was found in the DLC:Si film, in comparison with study by Cheng et al [25]. It was 16.49 and 2.1 at.%.…”
Section: Optical Propertiessupporting
confidence: 61%
“…Taking into account the properties mentioned above, the DLC nanocomposite films with embedded plasmonic Au, Ag, or Cu nanoparticles seem to be a prospective material for fabrication of the saturable absorbers. Having in mind the role of diamond-like carbon or graphite-like carbon particles in the absorbance self-saturation effect described in [25], one can expect tunable properties of DLC with embedded metallic nanoparticles. However, despite very intensive and numerous investigations on DLC films and DLC nanocomposites containing Au, Ag, or Cu, nonlinear optical properties including the saturable absorption effect of this material have not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the novel demonstration of a passively mode-locked erbium-doped fiber laser (EDFL) based on a nonstoichiometric silicon carbide (Si x C 1−x ) saturable absorber has been reported14. In particular, the authors have shown that when the C/Si composition ratio is increased to 1.83, the dominant absorption of the Si x C 1−x film changes from two-photon absorption (TPA) to nonlinear saturable absorption, and the corresponding TPA value falls to ~3.9 × 10 −6  cm/W.…”
mentioning
confidence: 99%